Incessant focal atrial tachycardia as a cause of cardiomyopathy. About a case - Muñoz Moreno, Juan Manuel (2021)
Focal atrial tachycardia is a rare type of supraventricular tachyarrhythmia, generally present in young people, and is a rare cause of tachycardiomyopathy (10%). We present a clinical case of tachycardiomyopathy in a 30-year-old man, without comorbidities, who was diagnosed with incessant focal atrial tachycardia, refractory to medical therapy, and electrical cardioversion. Succesful endocardial ablation was performed,  and in outpatient follow-up at 6 months, he showed a recovery of the left ventricular ejection fraction and reduction of the left chambers to normal ranges, with progressive decrease of dyspnea.